RECENT DEVELOPMENTS IN ACCOUNTING. - Werntz, William W. (The Accounting Review, 1947)
Abstract The article focuses on recent developments in accounting. The present age is an age of transition. Economic conditions prevalent in this transition period have been such as bring about a very large number of new registrations. In many cases, companies are taking advantage of current low interest and dividend rates to refinance their bond issues or to replace high-dividend preferred. Many more are seeking new capital for the first time, or at least for the first time in many years. In still other cases, the owners of closely-held businesses are seeking to sell part or all of their holdings to the public. In these last two groups are a great many small or medium-sized concerns in which there has never before been any major investment by the general public. Since a large percentage of the day-to-day accounting problems currently concern this type of case some typical accounting questions which such cases present can be outlined. In addition to their own special problems, the mine-run of such cases will include illustrations of nearly all of the major accounting problems arising in any of the accounting work.